Chaos and Its Influence on Children's Development: An Ecological Perspective.
DOI: 10.1037/12057-004
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of family chaos and its relation to children's socioemotional well-being.

Abstract: A discussion of chaos effects on child socioemotional well-being necessarily draws attention to family-level processes. Environmental chaos typically refers to disruptions in multiple domains, including sensory overload, physical crowding, and routine family life (Evans, Gonnella, Marcynyszyn, Gentile, & Salpekar, 2005;Matheny, Wachs, Ludwig, & Philips, 1995). When routines are diminished in frequency and family life is disorganized, questions about how the group works together collectively to promote and sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0
1

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 75 publications
3
89
0
1
Order By: Relevance
“…Variability in work schedules may lead to instability and chaos in family routines, further exacerbating negative child outcomes such as disruptions in school achievement, externalization of behavioral problems (Hsuch & Yoshikawa, 2007), and attention difficulties (Fiese & Winter, 2010). Hardway, Wilson, Shaw, and Dishion (2012) revealed that whereas positive behavior supports cultivation of the development of self-regulatory skills, household chaos acts as a deterrent to the development of many skills over time, stating that poor self-regulatory skills were related to increases in externalizing problems over time.…”
Section: Family Rolesmentioning
confidence: 97%
See 1 more Smart Citation
“…Variability in work schedules may lead to instability and chaos in family routines, further exacerbating negative child outcomes such as disruptions in school achievement, externalization of behavioral problems (Hsuch & Yoshikawa, 2007), and attention difficulties (Fiese & Winter, 2010). Hardway, Wilson, Shaw, and Dishion (2012) revealed that whereas positive behavior supports cultivation of the development of self-regulatory skills, household chaos acts as a deterrent to the development of many skills over time, stating that poor self-regulatory skills were related to increases in externalizing problems over time.…”
Section: Family Rolesmentioning
confidence: 97%
“…Hardway, Wilson, Shaw, and Dishion (2012) revealed that whereas positive behavior supports cultivation of the development of self-regulatory skills, household chaos acts as a deterrent to the development of many skills over time, stating that poor self-regulatory skills were related to increases in externalizing problems over time. Accumulations of stress, limited resources, and unpredictable work schedules are likely to account for the increased amount of chaos in economically strained households in comparison with more economic advantageous households (Fiese & Winter, 2010).…”
Section: Family Rolesmentioning
confidence: 99%
“…First, family routines and rituals are influenced by context more readily than other family processes (Fiese et al, 2002), and therefore are quickly adjusted to the demands and opportunities of living situations. Second, other family processes (such as parenting behaviors) are enacted during family routines and rituals, and so disruptions of routines and rituals likely lead to disruptions of other aspects of family life (Boyce et al, 1983; Denham, 1995; Fiese & Winter, 2010). Third, family routines and rituals make sense to families (Fiese et al, 2002).…”
Section: Background and Significancementioning
confidence: 99%
“…Increasing interest in the study of environmental chaos has been fueled by a growing body of research that has found negative associations between measures of cognitive or social-emotional development and exposure of infants and children to both higher levels of general chaos as well as to specific markers of home chaos (Ackerman & Brown, 2010;Asbury, Wachs, & Plomin, 2005;Brody & Flor, 1997;Dumas et al, 2005;Evans & Hygge, 2007;Evans & Stecker, 2004;Fiese & Winter, 2010;Hart, Petrill, Deater-Deckard, & Thompson, 2007;Johnson, Martin, Brooks-Gunn, & Petrill, 2008;Matheny & Phillips, 2001;Pike, Lervolin, Ely, Price, & Plomin, 2006;Tus-Sabah, Gilani, & Wachs, 2011). While higher levels of environmental chaos are more likely to occur in low income families (Ackerman & Brown, 2010;Evans, 2006) chaos is more than a proxy term for low family socioeconomic status (SES).…”
Section: Introductionmentioning
confidence: 98%